Identificación de relaciones entre los nodos de una red social - Barón, Mónica Andrea Niño; Ordóñez Salinas, Sonia (Ingeniería, 2013)
In this paper a review is conduced about representation and classifi cation of membership among nodes belonging to a social network. For this purpose, topics such as Natural Language Processing, Text Mining, Information Retrieval and Named Entities are considered description and survey of outstanding approaches is carry out in each topic.